THE EFFECT OF SHADE LEVEL AND GOAT MANURE DOSAGE ON YIELD OF STENO GRASS (Stenotaphrum secundatum) ON LATOSOL SOIL - B., Velani,; Wirawan, I W.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2024)
The success of ruminant livestock farming is greatly influenced by the availability of forage, especially during long dry seasons which reduce livestock growth and production. One solution to address forage shortages is to use steno grass ( Stenotaphrum secundatum ), which can adapt to various environmental conditions and serves as an alternative forage for livestock. The research aims to determine the effect of the level of shade and dose of goat manure as well as the interaction between the level of shade and the dose of goat manure on the yield of stenograss ( Stenotaphrum secundatum ) on latosol soil. This research was carried out in the greenhouse of Sading Village, Mengwi District, Badung Regency. The research lasted 12 weeks, using a completely randomized design (CRD) with a factorial pattern with two factors. The first factor is the level of shade, namely: N0 = 0%; N1 = 20%; N2 = 40%; and N3 = 60%. The second factor is the fertilizer dose: D1 = 10 tons ha-1; D2 = 20 tons ha-1; and D3 = 30 tons ha-1, there were 12 treatments and each treatment was repeated three times, so the number of experimental units was 36 pots. The variables observed are yield variables and plant growth characteristics. The results of the research showed that there was an interaction between the level of shade and the dose of goat manure on the dry weight of stems and total dry weight of forage. Providing shade levels reduces the yield of Stenotaphrum secundatum . Treatment dose of 30 tons ha-1 (D3) tends to give the best results of Stenotaphrum secundatum grass. t can be concluded that there is an interaction between the level of shade and the dose of goat manure on the dry weight of stems and total dry weight of forage variables. Providing a level of shade reduces the yield of Stenotaphrum secundatum grass on latosol soil and a treatment dose of 30 tons ha-1 (D3) tends to give the best yields of Stenotaphrum secundatum grass on latosol soil.